阿德勒鼓勵訓練方案對幼兒園教師的影響 A Study of the Impacts of Adlerian Encouragement Training Program on Kindergarten Teachers - 張英熙 Ying-Shi Chang (National Changhua University of Education, 2015)
本研究旨在探討阿德勒鼓勵訓練方案對幼兒教師的影響。以阿德勒五種鼓勵用語為訓練焦點的訓練方案，每週一次每次三小時為期六週。訓練活動包括分享童年鼓勵及挫折經驗、鼓勵原則與用語介紹、鼓勵實習及督導等。11 位女性幼兒園教師參與訓練，訓練末收集學員回饋單，進行三次焦點團體，並邀二位表達豐富者進行半 結構深度個別訪問。根據回饋單、焦點團體及個別訪談資料進行內容分析，發現鼓勵訓練對幼兒園教師的影響包括以下三大項：一、教師更善於鼓勵：鼓勵用語更具體多元、觀察更深廣、認同鼓勵原則、發展出正向管教策略及發展出深度鼓勵策略；二、教師更具鼓勵態度：發展出正向視框、更重視幼兒內在動機、更尊重個別 差異、更能接納幼兒及自我鼓勵；三、教師發展出人際關係鼓勵圈：建立更有效能的師生關係、因幼兒的信任而感動、教師角色更具彈性、親師生形成鼓勵圈及教師對工作更富熱情。最後，依據研究結果進一步提出實務及研究建議。 The purpose of this study was to explore the impacts of Adlerian Encouragement Training Program on kindergarten teachers. The six-week encouragement training program was designed based on Adlerian psychology, focusing on the use of encouragement language. The participants met once a week, three hours per meeting. The trainees were 11 female kindergarten teachers. The activities of training program included sharing encouraged and discouraged experiences in their childhood, learning the encouragement principles and language, practicing skills, and doing supervision. The researcher collected feed-back sheets in the sixth week and conducted three times of focus-group interview. Qualitative method of content analysis was used on feed-back sheets, focus-group interviews and individual interviews. The findings were: 1. Teachers were better at encouraging children through encouraging children with specific behavior description, a variety of encouragement language, and deeper observation, convincing themselves of the encouragement principles and developing both positive discipline strategies and encouraging strategies. 2. Teachers developed more encouraging attitude through constructing positive framework, valuing the intrinsic motivation of children and individual differences, as well as more accepting children and self-encouraging. 3. The interpersonal encouraging circle was built, observed by efficiency relationship between teacher-children was built, more children's closer behavior toward teachers, teachers' appreciation because of children's trust, the flexible role of teacher, encouraging circles developed among teacher, children and parents, and the increase of teachers' passion and enthusiasm. In the last section, suggestions for teacher training and further study were proposed.